Taxonomic study of the genus Eretmocera Zeller, 1852 (Lepidoptera: Scythrididae) from China, with descriptions of three new species - Lou, Kang; Yu, Dian; You, Wanxue; Li, Houhun (Zootaxa, 2019)
Four species of the genus Eretmocera Zeller, 1852 from China are reviewed. Three species are described as new: Eretmocera yingjiangensis Li, sp. nov., E. octopunctata Li, sp. nov. and E. artemisiae Li, sp. nov. Eretmocera impactella (Walker, 1864) is redescribed based on specimens founded on Yunnan, China. Photographs of adults and genitalia are provided, and a key to the Eretmocra species that occur in China is given.